Clinical and economic impact of generic versus brand name meropenem use in an intensive care unit in Colombia (2019)
Background Recent studies suggest that sustained use of generic antibiotics may be associated with clinical failure and emergence of antibacterial resistance. The present study was designed to determine the clinical outcome between the use of generic meropenem (GM) and brand-name meropenem (BNM). Additionally, this study evaluated the economic impact of GM and BNM to determine if the former represents a cost-effective alternative to the latter. Methods Patients treated between January 2011 and May 2014 received GM while patients treated between June 2014 and March 2017 received BNM. Mortality was compared between groups. Total infection cost was defined by the cost of antimicrobial consumption, length of stay, and laboratory and imaging exams until infection resolution. Findings A total of 168 patients were included; survival rate for the 68 patients treated with GM was 38% compared to 59% in the patients treated with BNM. Multivariate analysis showed that the variables most strongly-associated with mortality were cardiovascular disease (OR 18.18, 95% CI 1.25–262.3, p = 0.033) and treatment with generic meropenem (OR 18.45, 95% CI 1.45–232.32, p = 0.024). On the other hand, total infection cost did not show a significant difference between groups (BNM $10,771 vs. GM $11,343; p = 0.91). Interpretation The present study suggests that patients treated with GM have a risk of death 18 times higher compared to those treated with BNM. Furthermore, economic analysis shows that GM is not more cost effective than BNM. Summary More studies measuring clinical outcomes are needed to confirm the clinical equivalence of brand-name versus generic antibiotics, not only for meropenem but also for other molecules.